A novel love story [large type] - Poston, Ashley (Thorndike Press, a part of Gale, a Cengage Company, 2024)
Eileen Merriweather loves a good love story. The fictional kind, anyway. After all, imaginary men don't break your heart. That's why she's so excited for her annual book club retreat - instead, when her car breaks down en route, Eileen finds herself in Eloraton. A town where every meet is cute, the rain always comes in the afternoon, and the bookshop is always curated with impeccable taste. It feels too good to be true because Eloraton is the setting of her favourite romance series. And Eileen is sure she must be here to bring the town its storybook ending. But there's one character she can't place. The grumpy bookshop owner with mint-green eyes, and an irritatingly sexy mouth. He does not want Eileen to finish this story, but how else can she find her happily-ever-after?